A Mixed Study on the School Head's and Teacher's Self-Efficacy and School Performance: An Input for Policy Enhancement for Social Media Learning in the Philippines during the New Normal (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
The emergence of the COVID-19 pandemic created a radical transformation in teaching-learning in schools worldwide. This phenomenon challenged the self-efficacy of teachers and school heads in public schools in the Philippines, specifically on how to apply social media learning, which is a new modality. Through a mixed research method, 232 schoolteachers and 26 school heads participated in answering an adopted modified questionnaire; and ten school personnel participated in answering a researcher-made interview guide. The findings showed that profile variables such as age, sex, educational background, and length of service did not significantly correlate with school performance. In contrast, the challenges associated with self-efficacy in terms of educational management, instructional leadership, moral leadership, and application of social media learning tools were all significantly correlated with school performance. This indicated that self-efficacy improves school performance in both teachers and school heads and is influenced by their positive and healthy attitudes. From the qualitative data, the derived themes have implications with economic conditions, knowledge, and skills on the application of technology, transfer of knowledge to students, maintaining coordination, collaboration, and support from educational stakeholders, curriculum design and adherence with educational standards, imposing disciplinary measures, and compliance with school requirements. Officials in the educational setting should consider upgrading policies on personnel capability and capacity building, enhancing professional development, and equipping them with the application of modern teaching methods. All these concepts were considered in a proposed recommendation to the Department of Education, Philippines, for policy enhancement.